Paradoxical Agitation and Masseter Spasm During Propofol Procedural Sedation: A Case Report - Amit S Padaki; Prabhdeep Uppal; Michael Perza (Clinical Practice and Cases in Emergency Medicine)
Introduction: Propofol is an anesthetic agent commonly used in emergency department (ED) procedural sedation. It is often preferred in orthopedic procedures because of its muscle-relaxing properties. Rarely, however, it can induce agitation and muscle hypertonicity. Case Report: A 58-year-old man presented to the ED with a left ankle fracture-dislocation. Propofol was used to facilitate procedural sedation, but the patient became mildly agitated. Ketamine was used to achieve full induction, after which propofol was used again to facilitate muscle relaxation. Near the end of the procedure, the patient had opisthotonos and masseter spasm requiring bag-valve-mask ventilation and subsequent intubation. This reaction was ultimately attributed to adverse effects of the propofol. Conclusion: While propofol is generally well tolerated, it can potentially cause agitation, hypertonicity, and other side effects such as muscle spasms and seizure-like activity. Acknowledging and preparing for these risks can potentially improve patient outcomes.